2013
DOI: 10.1177/0731684412454462
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aqueous extraction on the performance and properties of polypropylene/wood composites from Phoenix dactylifera and Acacia tortilis wood

Abstract: Polypropylene/wood composites were prepared by melt blending technique using a twin screw extruder and subsequently ASTM samples were also prepared by injection molding technique. Untreated and pre-treated particles of Phoenix dactylifera and Acacia tortilis woods are used in this study to investigate the effect of pre-treatments on the different properties of polypropylene/wood composites. The tensile strength of the wood composites was evaluated by ASTMD-638 method and it was found to be higher than the neat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
(58 reference statements)
2
7
0
Order By: Relevance
“…These values are close to the values obtained on midribs of five date palm cultivars [7], and on some lignocellulosic residues [36], while they are lower than those reported for date palm trunk (PT) and rachis [11]. There is very little information to compare chemistry of the different parts of date palm residues, but the results found in this work are in partial agreement with previously published studies on non-identified date palm cultivars [17,50].…”
Section: Discussionsupporting
confidence: 90%
“…These values are close to the values obtained on midribs of five date palm cultivars [7], and on some lignocellulosic residues [36], while they are lower than those reported for date palm trunk (PT) and rachis [11]. There is very little information to compare chemistry of the different parts of date palm residues, but the results found in this work are in partial agreement with previously published studies on non-identified date palm cultivars [17,50].…”
Section: Discussionsupporting
confidence: 90%
“…These values are close to the values obtained by Hindi et al (2010) and Nasser and Al-Mefarrej (2011). In general, these results are in agreement with previously published studies in non-identified date palm cultivars (Hindi et al 2010;Aref et al 2013). Each value is an average for 24 specimens ± standard deviation.…”
Section: Chemical Analysis Of the Date Palm Midribssupporting
confidence: 93%
“…For many years humans have obtained food, cover and building materials, fuel, and a source of warmth in the winter from the date palm tree (Al-Fuhaid 2006). Date palm residues have been used as a source of raw materials for the wood industry for the production of pulp and paper (Khiari et al 2011), particleboard (Hegazy and Aref 2010), wood-plastic composites (Aref et al 2013), woodcement composites (Nasser and Al-Mefarrej 2011), and lumber-like products (El-Mously 1997). Date palm residues have also been considered as an available source for wood industries in Saudi Arabia (Nasser and Al-Mefarrej 2011;Hegazy and Aref 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The soluble amount of extractives, mainly sugars in hot water and cold-water extraction, were 21.65% and 15.28%, respectively (Nasser and Al-Mefarrej 2011;Aref et al 2013). In addition, with different varieties of date palm, the total extractives' contents ranged from 19.3% to 21.7% and ash contents ranged from 3.3% to 5.8% (Nasser 2014).…”
Section: Sem-edx Analyses Wpcs Made From Date Palm Midrib With T Harmentioning
confidence: 99%
“…Residues of date palm (Phoenix dactylifera L.) can be used for several industrial purposes, such as the production of particleboards (Hegazy and Aref 2010;Amirou et al 2013), energy production (Nasser et al 2016), pulp and paper (Khristova et al 2005;Nasser et al 2015), wood-cement composites (Nasser and Al-Mefarrej 2011), and woodplastic composites (Abu-Sharkh and Hamid 2004;Aref et al 2013;Nasser and Aref 2014). -20/+40-mesh (passed through 20-mesh and retained on 40-mesh) Pretreatments Control (wood particles without any pretreatments), cold water extraction (soaked for 48 h at 27±5°C), and hot water extraction (boiling in water for 6 h with changing water every 2 h at 70±5 °C) (Moslemi et al 1983 The WPCs made from untreated date palm and polypropylene without maleic acid modified polypropylene "MAPP" (DP-UN-PP), date palm pretreated by cold water extraction and polypropylene without MAPP (DP-CWE-PP), and date palm pretreated by hot water extraction and polypropylene without MAPP (DP-HWE-PP) were used (Nasser and Aref 2014).…”
Section: Introductionmentioning
confidence: 99%